The Influence of Organizational Culture, Work Discipline and Work From Home on The Productivity of Civil Servants at The Public Works Office : Pengaruh Budaya Organisasi, Disiplin Kerja dan Work From Home terhadap Produktivitas Kerja Pegawai Negeri Sipil pada Dinas Pekerjaan Umum - Nurhayati, Isma Dewi; Sari, Dewi Komala (Indonesian Journal of Law and Economics Review, 2023)
This research aims to find out the influence of Organizational Culture on employee work productivity.To find out the effect of work discipline on employee work productivity. To find out the effect of Work From Home on employee work productivity.And to find out the influence of Organizational Culture, Work Discipline and Work From Home simultaneously on employee work productivity in the Pu Bina Marga Prov Jatim Office. This type of research is a study that uses quantitative methods.The location of the study this time, researchers took objects at the Pu Bina Marga Prov Jatim Office.The population used in this study was 134 employees, with sampling that is Simple Random Sampling.There were 100 respondents. Data collection using questionnaires. Data analysis using multiple linear regression analysis. The results showed that organizational culture has an effect on employee work productivity.Work discipline affects employee productivity. Work From Home affects employee work productivity and Organizational Culture, Work Discipline and Work From Home simultaneously affect employee work productivity in PU Bina Marga East Java Province